If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8w+10=-6(w-3)
We move all terms to the left:
-8w+10-(-6(w-3))=0
We calculate terms in parentheses: -(-6(w-3)), so:We get rid of parentheses
-6(w-3)
We multiply parentheses
-6w+18
Back to the equation:
-(-6w+18)
-8w+6w-18+10=0
We add all the numbers together, and all the variables
-2w-8=0
We move all terms containing w to the left, all other terms to the right
-2w=8
w=8/-2
w=-4
| 3m+100=438 | | 1/2x-5=-8 | | b÷4=32 | | -35+3x=45+5x | | 12/72=x/12 | | -4/3w+17=11 | | 1/5(20-5y)=6 | | 10y+25=45 | | 3+3(3x-6)=5-4(2x+1) | | 3v=4v−10 | | 3x62/5=13 | | 6=8-c | | 4(3x-)=16 | | -8u+6(u-2)=-14 | | 8d-4d+5=-3 | | 3=3u−6 | | -24-1-8p=3-8p=41 | | 7-(2n+1)=·8n | | 48b+185=2,000 | | n=10/5=5 | | 87+t=23 | | −3(x−1)=21 | | 12-7+3x=25 | | 4x=48-2x² | | T=-16t^2+105 | | -3p-1=29 | | 95-r=42 | | -125=n-58 | | 4x-6+4x-6+24=36 | | 5+x÷3=-25 | | -4x+10=5-8x | | 39-6x=120+26x |